Fatigue in autoimmune skin diseases. (3rd June 2019) - Tarazi, M.; Gaffney, R.G.; Pearson, D.; Kushner, C.J.; Werth, V.P.
Summary: People with the disease systemic lupus erythematosus (SLE) often suffer from fatigue, reducing quality of life and contributing to ill health. The authors of this study, based in Pennsylvania and New Jersey, USA, studied whether fatigue was a feature in other autoimmune skin conditions. Autoimmune means when the body's immune system, which usually fights off infection, actually targets healthy cells. They used a 36‐item questionnaire (SF‐36), with a specific vitality scale to measure levels of fatigue in controls (people without SLE) and patients with SLE, and the diseases chronic cutaneous LE, amyopathic dermatomyositis and autoimmune blistering conditions. Levels of fatigue were worst in the patients with SLE, but all the other conditions studied were linked with greater fatigue than the control group. The levels of fatigue were similar in the groups with dermatomyositis and blistering conditions, but less in the patients with cutaneous LE. The authors conclude that fatigue is an important feature of these autoimmune conditions, and is detrimental to quality of life. Abstract : Linked Article: Tarazi et al. Br J Dermatol 2019; 180 :1468–1472